Instructor's pedagogical content knowledge, student's entrepreneurial personality and learning style as predictors of entrepreneurial intention among community college students - Sipon, Merhayati; Lope Pihie, Zaidatol Akmaliah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Looking at broad perspective, we can conclude that education is about learning where most people agree that qualification (certificate or degree) are the products of that learning. If we as an educator think more in depth, we see that a higher grade or score in examinations cannot be the truest indicator to state that the students or graduate have become effective and independent learner. Similar as in this case of study, the more students or graduates that we train or taught in entrepreneurship education, it will not produce the same number of entrepreneurs. Yet the product (targeted number of entrepreneurs) out of the whole programs were still low due to many factors. Some factors such as how knowledgeable and experiences are the instructors in the subject matter and content knowledge and the students personality in creating their own entrepreneurial learning style will determine how deep is the student’s entrepreneurial intention. This paper will discuss further on the role of instructor’s pedagogical content knowledge, student’s entrepreneurial personality and learning style in predicting entrepreneurial intention among students at community colleges. Thus, an appropriate training- teaching-learning in entrepreneurship education at community college could be obtain to get more promising outcome.